The Complete Book of Scriptwriting - Straczynski, J. Michaefrey50 (Cincinnati, Ohio Writer's Digest Books, 1996)
Discusses all aspects of the scriptwriting business, including how to strengthen your writing technique, script format, finding a reliable agent, and much more.
Part 1 Television Chapter 1 A brief history of television, Chapter 2 The writer, the language, the formats, Chapter 3 The craft of telescripting, Chapter 4 Marketing the television script, Chapter 5 A look at the future. Part 2 Motion Picture Chapter 6 A brief history of motion pictures, Chapter 7 The benefits and drawbacks of screenwriting, Chapter 8 the art of the screenplay, Chapter 9 The craft of screenwriting, Chapter 10 The screenplay, Chapter 11 Marketing the screenplay. Part 3 Animation Chapter 12 Animation: Past, Present, and Future, Chapter 13 The art and craft of the animation script, Chapter 14 Marketing the animated script. Part 4 Radio Chapter 15 Radiodrama scripting: past, present, future, Chapter 16 The art and craft of Radiodrama scripting, Chapter 17 Marketing the radiodrama script. Part 5 The Stage Play Chapter 18 Writing for the stage: past, present, and future, Chapter 19 The art and craft of the stage play, Chapter 20 Marketing the stage play. Part 6 The business of scriptwriting Chapter 21 Warning Signs, Chapter 22 The writers guild of America, Chapter 23 The art of getting keeping an Agent
Includes index.
Keywords: Playwriting; Television authorship; Motion picture authorship; Radio authorship